Addressing pollution challenges for enterprises under diverse extreme climate conditions: artificial intelligence-driven experience and policy support of top Chinese enterprises - Sun, Jingjing; Guan, Xin; Zeng, Yanzhao; Zhang, Jiali; Chen, Xiaodie; Zhan, Xi (Frontiers in Public Health, 2024)
This study explores the experiences of leading Chinese companies in environmental conservation amid varying extreme climate conditions, emphasizing the roles of artificial intelligence (AI) and governmental assistance. A survey involving 200 participants revealed a widespread recognition of Tencent’s green initiatives and a robust endorsement for AI’s role in environmental protection. Additionally, a considerable number of firms are contemplating the adoption of AI technologies to enhance environmental management practices. Initiatives such as optimizing energy management, deploying intelligent HVAC (Heating, Ventilation, and Air Conditioning) systems, and improving operations of data centers and smart lighting systems are already underway. The findings suggest a strong belief in the potential for AI to further advance environmental protection efforts, with a call for increased governmental backing to nurture this development. Given these insights, the future of AI in environmental protection appears bright, underscored by the essential role of policy support from governments. It’s crucial, therefore, for both businesses and governments to forge a partnership focused on leveraging AI for environmental sustainability, contributing significantly to conservation efforts.